Numerical Exploration of Influence of Phase Changing Material in Heat Transfer Augmentation in the Double Tube Heat Exchanger - Gnanavel, C; Saravanan, R; Chandrasekaran, M (International Journal of Engineering and Technology, 2018)
The double tube heat exchanger is a device in which the inner tube carries the hot fluid.Â Phase Changing Material is the energy storage device is used for Solar heater applications to maintain the constant temperature, in the present study of this work is CFD Analysis of plain tube heat exchanger with Phase Changing Material (PCM) and without Phase Changing Material (PCM), Charging time, liquid volume fraction with the various Heat Transfer Fluid (HTF) inlet temperature 70, 75, 80 deg Celsius and various flow conditions of laminar flow of 2000 Re, Transition flow of 4000 Re and Turbulent flow of 10,000 ReÂ Â